2021
DOI: 10.3390/cancers13122884
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Thromboprophylaxis on the Survival of Patients with Advanced Pancreatic Cancer. The Pancreatic Cancer and Tinzaparin (PaCT) Study

Abstract: Pancreatic cancer (PaC) induces a prothrombotic and hypercoagulable state. The aim of this study was to investigate the effect of tinzaparin in combination with chemotherapy. The PaCT (pancreatic cancer and tinzaparin) study was a retrospective observational study that collected data regarding progression free survival (PFS) in advanced or metastatic PaC patients who received thromboprophylaxis with tinzaparin during chemotherapy with nab-paclitaxel (N) and gemcitabine (G). The primary end point was to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Preincubation of the chemoresistant A2780cis cell line led to sensitization to cisplatin [ 132 ] possibly through the Wnt signaling pathway [ 133 ]. Karamouzis et al demonstrated in a recent meta-analysis that the administration of tinzaparin in patients diagnosed with advanced pancreatic cancer increased the disease-free period by 39.5% compared to the population that did not receive the drug [ 134 ]. Enoxaparin was found to inhibit the CXCL12-driven proliferation, adhesion, and colony formation of human colon cancer HCT-116 cell line and suppressed the formation of metastases in Balb/C mice [ 135 ].…”
Section: Injectablesmentioning
confidence: 99%
“…Preincubation of the chemoresistant A2780cis cell line led to sensitization to cisplatin [ 132 ] possibly through the Wnt signaling pathway [ 133 ]. Karamouzis et al demonstrated in a recent meta-analysis that the administration of tinzaparin in patients diagnosed with advanced pancreatic cancer increased the disease-free period by 39.5% compared to the population that did not receive the drug [ 134 ]. Enoxaparin was found to inhibit the CXCL12-driven proliferation, adhesion, and colony formation of human colon cancer HCT-116 cell line and suppressed the formation of metastases in Balb/C mice [ 135 ].…”
Section: Injectablesmentioning
confidence: 99%
“…In addition, PaCT (Pancreatic Cancer and Tinzaparin) is a retrospective observational study conducted in 110 patients with advanced or metastatic pancreatic cancer with the aim of examining the anticancer effect of tinzaparin. The patients receiving “hyper-prophylactic” dose of tinzaparin (10000 anti-Xa IU/die) during chemotherapy with nab-paclitaxel and gemcitabine had 39.5% higher progression-free survival compared to patients without tinzaparin ( P < 0.05) [ 51 ]. However, overall, evidence on the antitumoral activity of LMWH is still contradictory and not conclusive.…”
Section: Evidence In Cancer-associated Thrombosismentioning
confidence: 99%
“…Reasoned by the elevated incidence, low molecular weight heparins (LMWH) are the guideline based drug for prevention and therapy of venous thromboembolism in cancer patients [ 19 ]. Since some clinical trials observed additional survival benefits for LMWH treated patient subgroups, while others did not, there is an ongoing debate whether LMWH exerts anti-metastatic effects beside its anticoagulant properties [ 20 22 ]. Thus, several metastasis-related targets of heparin have been postulated and are currently in debate [ 23 ].…”
Section: Introductionmentioning
confidence: 99%